2016
DOI: 10.1093/gbe/evw167
|View full text |Cite
|
Sign up to set email alerts
|

Genes Translocated into the Plastid Inverted Repeat Show Decelerated Substitution Rates and Elevated GC Content

Abstract: Plant chloroplast genomes (plastomes) are characterized by an inverted repeat (IR) region and two larger single copy (SC) regions. Patterns of molecular evolution in the IR and SC regions differ, most notably by a reduced rate of nucleotide substitution in the IR compared to the SC region. In addition, the organization and structure of plastomes is fluid, and rearrangements through time have repeatedly shuffled genes into and out of the IR, providing recurrent natural experiments on how chloroplast genome stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
55
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(68 citation statements)
references
References 39 publications
7
55
0
2
Order By: Relevance
“…A hallmark of gene conversion between repeated sequences is elevated GC content (Mugal et al, 2015). Recent studies have demonstrated that in addition to suppression of nucleotide substitution rates relative to single copy sequence, IR sequences experience GC‐biased gene conversion (Wu and Chaw, 2015; Li et al, 2016). The GC content of the M. emarginata plastome overall was high relative to typical land plants (mean 37.6%, >1000 species, Weng et al, 2016 a ) at 40.2%, yet it is not elevated relative to some other plastomes with atypical structure, i.e., long branch clade (LBC) Erodium (mean 44.1%, Blazier et al, 2016a) and Silene L. (mean 40.4%, calculated from complete plastomes on GenBank accessed 28 November 2016).…”
Section: Discussionmentioning
confidence: 99%
“…A hallmark of gene conversion between repeated sequences is elevated GC content (Mugal et al, 2015). Recent studies have demonstrated that in addition to suppression of nucleotide substitution rates relative to single copy sequence, IR sequences experience GC‐biased gene conversion (Wu and Chaw, 2015; Li et al, 2016). The GC content of the M. emarginata plastome overall was high relative to typical land plants (mean 37.6%, >1000 species, Weng et al, 2016 a ) at 40.2%, yet it is not elevated relative to some other plastomes with atypical structure, i.e., long branch clade (LBC) Erodium (mean 44.1%, Blazier et al, 2016a) and Silene L. (mean 40.4%, calculated from complete plastomes on GenBank accessed 28 November 2016).…”
Section: Discussionmentioning
confidence: 99%
“…For phylogenetic analyses, we included only protein‐coding genes that were consistently present in the single copy regions (SC) across all sampled plastomes. Loci that had moved into or out of the IR were excluded because they exhibit significant substitution rate heterogeneities (Li et al., ). In total, 71 genes were included.…”
Section: Methodsmentioning
confidence: 99%
“…Plastomes of photoautotrophic land plants typically range from 120 to 160 kb in length, with c. 80 protein-coding genes, four rRNAs, and c. 30 tRNAs arranged into a structure that usually includes large and small single-copy (SC) regions (termed LSC and SSC) separated by a large inverted repeat (IR) in two copies (Wicke et al, 2011;Jansen & Ruhlman, 2012;Mower & Vickrey, 2018). One of the most notable effects of this genomic structure is that substitution rates are several times lower in the IR relative to SC regions (Wolfe et al, 1987;Perry & Wolfe, 2002;Li et al, 2016;Zhu et al, 2016). This reduction in IR substitution rates has been attributed to a copy-dependent repair mechanism such as biased gene conversion (Birky & Walsh, 1992), which may be facilitated by frequent intramolecular recombination between IR copies that produces two isomeric forms of the plastome (Bohnert & Loffelhardt, 1982;Palmer, 1983).…”
Section: Introductionmentioning
confidence: 99%